Cryptococcal Antigen in Serum and Cerebrospinal Fluid for Detecting Cryptococcal Meningitis in Adults Living With Human Immunodeficiency Virus: Systematic Review and Meta-Analysis of Diagnostic Test Accuracy Studies. (23rd August 2020) - Temfack, Elvis; Rim, Jean Joel Bigna; Spijker, Rene; Loyse, Angela; Chiller, Tom; Pappas, Peter G; Perfect, John; Sorell, Tania C; Harrison, Thomas S; Cohen, Jérémie F; Lortholary, Olivier
Abstract: Cryptococcal antigen (CrAg) detection could direct the timely initiation of antifungal therapy. We searched MEDLINE and Embase for studies where CrAg detection in serum/cerebrospinal fluid (CSF) and CSF fungal culture were done on adults living with human immunodeficiency virus (HIV) who had suspected cryptococcal meningitis (CM). With Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2), we evaluated the risk of bias in 11 included studies with 3600 participants, and used a random-effects meta-analysis to obtain summary sensitivity and specificity of serum and CSF CrAg, as well as agreement between CSF CrAg and CSF culture. Summary sensitivity and specificity of serum CrAg were 99.7% (97.4–100) and 94.1% (88.3–98.1), respectively, and summary sensitivity and specificity of CSF CrAg were 98.8% (96.2–99.6) and 99.3% (96.7–99.9), respectively. Agreement between CSF CrAg and CSF culture was 98% (97–99). In adults living with HIV who have CM symptoms, serum CrAg negativity may rule out CM, while positivity should prompt induction antifungal therapy if lumbar puncture is not feasible. In a first episode of CM, CSF CrAg positivity is diagnostic. Abstract : In patients with symptoms suspicious of cryptococcal meningitis (CM) associated with human immunodeficiency virus, a positive serum cryptococcal antigen (CrAg) is highly presumptive of culture-confirmed CM and a positive cerebrospinal fluid CrAg is diagnostic of a first episode of CM.